Knowledge Transfer in Cynefin Framework - Harris Turino; Adhi Setyo Santoso (Sekolah Tinggi Manajemen IPMI, 2020)
The Cynefin model (Kurtz & Snowden, 2003) is a common concept for designing the most logical response from decision-makers in certain situations. This model is general, so it can be used in several applications, such as knowledge transfer, which is the focus of this article. The author aims to describe in detail, both the characteristics of the domain and the decision-making model, with the concept of causal ambiguity (Reed & Defillippi, 1990), absorptive capacity (Zahra & George, 2002), and pragmatic view of knowledge (Carlile, 2004). One of the managers' common mistakes in managing organizational knowledge is the failure to identify situations accurately. Using the case study method, the results of this study are expected to help practitioners minimize these mistakes and determine the right decisions in forming a sustainable competitive advantage (SCA). The discussion of this paper is divided into several sections; dynamics of cynefin model, absorptive capacity, pragmatic view of knowledge, integration of concepts, and conclusions.